Characterisation of cement-treated crushed rock basecourse for Western Australian roads - Yeo, Yang Sheng (Curtin University, 2011)
Cement treatment for pavement basecourse materials results in the creation of cement treated basecourse which is either classified as "modified" or "stabilised". The two classifications perform differently in service, with susceptibility to fatigue being the most obvious characteristic delineating the two. This classification methodology is currently quantified based on Unconfined Compressive Strength (UCS) ranges.Throughout the 1990s to the early 2000s, Main Roads Western Australia (MRWA) has investigated various basecourse products created by adding cement. However, due to unexpected behaviour when applying the cement treated basecourse materials, MRWA sanctioned restrictions of its use in Western Australia. "Stabilised" basecourse were not to be used on roads and strength gained from "modified" basecourse is to be ignored. This is quantified by measuring the UCS gained from the cement treatment.Nevertheless, using UCS to classify cement treated crushed rock is injudicious and does not portray the insitu behaviour and characteristics of cement treated crushed rock basecourse. This dissertation therefore investigates the characteristics of cement treated crushed rock basecourse for Western Australian roads. This is to determine a better method to quantify the various classification of cement treated basecourse and understand its insitu behaviour. Subsequently, the result provides encouragement to reintroduce the use of cement treated crushed rocks in Western Australia.Amongst the characteristics investigated are strength, fatigue, shrinkage, durability and erodibility. These characteristics are assessed against varying cement content. The dissertation combines known standard testing methods along with uniquely developed testing methods to establish numerical models for characterising the materials. This includes the application of the Four Point Bending Test for fatigue, Tube Suction Test for durability, Nitrogen Adsoprtion for shrinkage, and Wheel Tracking Test for erodibility. A finite element model is also created to validate the results for fatigue.This dissertation has improved the understanding of the cement treated crushedrock materials. It proposes a new numerical fatigue model and provides an alternative classification methodology by incorporating the other key characteristics studied by this paper.